Naringenin-Grafted Polyvinyl Alcohol (Na/PVA) Nanoparticles: Synthesis, Characterisation and in vitro Evaluation of Its Antimicrobial Efficiency on Fresh Beef - Syarifah Ab Rashid; Nur Suhaili Mohamad Rosli; Teo Siew Hway; Tong Woei Yenn; Leong Chean Ring; Fahmi Asyadi Md Yusof; Tan Wen-Nee (Tropical Life Sciences Research, 2022)
Food preservatives are commonly used to guarantee the safety and quality of food. Naturally-derived preservatives are preferred by the consumers as chemical preservatives are associated with adverse side effects. The application of naringenin as a food preservative is restricted due to its high volatility, albeit known for its good efficacy in inhibiting microbial growth on food. Thus, this study aimed to synthesis and characterise naringenin-grafted PVA (Na/PVA) nanoparticles as potential meat preservative. The nano-size of naringenin was characterised by transmission electron microscopy. Finally, the antibacterial efficiency of Na/PVA nanoparticles substance was evaluated on disc diffusion assay, broth microdilution assay and using fresh beef as food model. The naringenin nanoparticles appeared in globule and smooth structure, with an average size of less than 200 nm. In total, 11.08% of naringenin nanoparticles was successfully encapsulated into PVA nanoparticles. Based on Fourier transform infrared spectra, naringenin was successfully encapsulated into PVA nanoparticles. The release of naringenin from Na/PVA nanoparticles was slow and gradual, with an initial burst release effect observed. The property was ideal for application in food model. It gained a plateau at 48 h. The Na/PVA nanoparticles depicted its antibacterial efficiency on all the test foodborne bacteria, except E. coli. It was represented by the presence of inhibition zones, which were ranged from 10 mm to 14 mm. The activity was concentration-dependent, and a higher concentration of nanoparticles was needed to kill the test bacteria. The meat coated with Na/PVA nanoparticles displayed a 100% reduction in bacterial load, where no bacterial growth was detected at the sample throughout the incubation period. The coating of nanoparticles also improved the organoleptic property of fresh beef, by maintain the meat colour. The developed nanoparticles can be potentially used nano-preservative to maintain the microbiological quality of fresh beef. Pengawet makanan biasanya digunakan untuk menjamin keselamatan dan kualiti makanan. Pengawet semulajadi yang diperoleh ialah pilihan oleh pengguna kerana pengawet kimia dikaitkan dengan kesan sampingan yang buruk. Penggunaan naringenin sebagai pengawet makanan adalah terhad kerana turun naik yang tinggi, walaupun dikenali kerana keberkesanan yang baik dalam menghalang pertumbuhan mikrob pada makanan. Oleh itu, kajian ini bertujuan untuk mensintesis dan mencirikan nanozarah PVA (Na/PVA) naringenin sebagai pengawet daging yang berpotensi. Saiz nano naringenin dicirikan oleh mikroskopi elektron penghantaran. Akhirnya, kecekapan antibakteria bahan nanozarah Na/PVA dinilai pada disc diffusion assay, broth microdilution assay dan menggunakan daging lembu segar sebagai model kajian. Naringenin nanozarah muncul dalam globul dan struktur licin, dengan saiz purata kurang daripada 200 nm. Secara keseluruhan, 11.08% daripada naringenin nanozarah telah berjaya dimasukkan ke dalam nanozarah PVA. Berdasarkan pengubah spektra inframerah Fourier, naringenin berjaya dikapsulkan dalam nanozarah PVA. Pelepasan naringenin dari Na/PVA nanozarah adalah perlahan dan beransur-ansur, dengan kesan pelepasan mendadak diperhatikan pada fasa awal kajian. Sifat ini sesuai digunakan untuk menghalang pertumbuhan mikrob pada makanan. Ia mendapat dataran tinggi pada 48 h. Nanozarah Na/PVA menggambarkan kecekapan antibakteria pada semua bakteria bawaan makanan ujian, kecuali E. coli. Ia diwakili oleh kehadiran zon perencatan, yang berkisar dari 10 mm hingga 14 mm. Aktiviti ini bergantung kepada kepekatan, dan kepekatan nanozarah yang lebih tinggi diperlukan untuk membunuh bakteria ujian. Daging yang disalut dengan Na/PVA nanozarah menunjukkan pengurangan 100% dalam beban bakteria, di mana tiada pertumbuhan bakteria dikesan pada sampel sepanjang tempoh inkubasi. Lapisan nanozarah juga meningkatkan sifat organoleptik daging lembu segar, dengan mengekalkan warna daging. Nanozarah yang dibangunkan berpotensi digunakan nano-pengawet untuk mengekalkan kualiti mikrobiologi daging lembu segar.